1-(3-mesityl-3-methylcyclobutyl)-2-(pyrrolidin-1-yl)ethan-1-one - Dinçer, M; Özdemir, N; Çukurovali, A; Yilmaz, I; Büyükgüngör, O (Int Union Crystallography, 2004)
In the title molecule, C20H29NO, the cyclobutane ring is puckered, with a dihedral angle of 19.8 (3) degrees between the two planes. The pyrrolidine ring adopts an envelope conformation. There are intermolecular C-H...O and C-H...pi interactions.